Single-Molecule Force Spectroscopy on the N2A Element of Titin: Effects of Phosphorylation and CARP - Lanzicher, Thomas; Zhou, Tiankun; Saripalli, Chandra; Keschrumrus, Vic; Smith III, John E.; Mayans, Olga; Sbaizero, Orfeo; Granzier, Henk (Frontiers in Physiology, 2020)
Titin is a large filamentous protein that forms a sarcomeric myofilament with a molecular spring region that develops force in stretched sarcomeres. The molecular spring has a complex make-up that includes the N2A element. This element largely consists of a 104 residue unique sequence (N2A-Us), flanked by immunoglobulin domains (I80 and I81). The N2A element is of interest because it assembles a signalosome with CARP (Cardiac Ankyrin Repeat Protein) as an important component; CARP both interacts with the N2A-Us and I81 and is highly upregulated in response to mechanical stress. The mechanical properties of the N2A element were studied using single molecule force spectroscopy, including how these properties are affected by CARP and phosphorylation. Three protein constructs were made that consisted of 0, 1, or 2 N2A-Us elements with flanking I80 and I81 domains, and with specific handles at their ends for study by atomic force microscopy (AFM). The N2A-Us behaved as an entropic spring with a persistence length (Lp) of 0.35 nm and contour length (Lc) of 39 nm. CARP increased the Lp of the N2A-Us and the unfolding force of the Ig domains; force clamp experiments showed that CARP reduced the Ig domain unfolding kinetics. These findings suggest that CARP might function as a molecular chaperone that protects I81 from unfolding when mechanical stress is high. The N2A-Us was found to be a PKA substrate and phosphorylation was blocked by CARP. Mass spectrometry revealed a PKA phosphosite (Ser-9895 in NP_001254479.2) located at the border between the N2A-Us and I81. AFM studies showed that phosphorylation affected neither the Lp of the N2A-Us nor the Ig domain unfolding force (Funfold). Simulating the force–sarcomere length relation of a single titin molecule containing all spring elements showed that the compliance of the N2A-Us only slightly reduces passive force (1.4%) with an additional small reduction by CARP ( 0.3%). Thus, it is improbable that the compliance of the N2A element has a mechanical function per se. Instead it is likely that this compliance has local effects on binding of signaling molecules and that it contributes thereby to strain- and phosphorylation- dependent mechano-signaling.